2017
DOI: 10.1177/1541931213601831
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Uncertainty Aids Spatial Judgments but Fails to Improve Metacognitive Efficiency

Abstract: Uncertainty is an element of many decision-making tasks and inherently compromises performance. Research has found only equivocal evidence that uncertainty representations—displays that explicitly denote data quality—offset the performance costs of uncertainty. As yet, though, no work has examined the potential benefits of uncertainty displays to metacognition, display readers’ ability to assess the quality of their own decision-making processes. The current study examined the benefits of uncertainty visualiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Decision-making is the process of identifying and choosing among competing courses of action (Padilla et al, 2018). Recent studies have focused on the use of uncertainty information to support decision making, and several papers have shown that decision-making accuracy can be improved when individuals are provided with uncertainty information compared to when they are not (Burton et al, 2017;Fernandes et al, 2018;Nadav-Greenberg & Joslyn, 2009). Furthermore, Joslyn and LeClerc (2012) found that providing explicit advice about which outcome to choose does not necessarily result in better decision-making performance than providing uncertainty information.…”
Section: Decision Makingmentioning
confidence: 99%
See 2 more Smart Citations
“…Decision-making is the process of identifying and choosing among competing courses of action (Padilla et al, 2018). Recent studies have focused on the use of uncertainty information to support decision making, and several papers have shown that decision-making accuracy can be improved when individuals are provided with uncertainty information compared to when they are not (Burton et al, 2017;Fernandes et al, 2018;Nadav-Greenberg & Joslyn, 2009). Furthermore, Joslyn and LeClerc (2012) found that providing explicit advice about which outcome to choose does not necessarily result in better decision-making performance than providing uncertainty information.…”
Section: Decision Makingmentioning
confidence: 99%
“…Metacognition enables individuals to assess the quality of their own cognition, regulate it effectively, and learn the correct approach for their future performances (Burton et al, 2017). A review of literature showed three categories of metacognitive tasks that can be applied to uncertainty visualizations: Self-Monitoring, Metacognitive Control, and Self-Regulated Learning (Schraw & Moshman, 1995;Winne & Azevedo, 2014).…”
Section: Metacognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Matejka and Fitzmaurice (2017a) illustrated this same point compellingly with a more sophisticated simulated annealing technique. 2 They further demonstrated that depending on the type of visualization, the representation of data dispersion and uncertainty may be inherently occluded. As illustrated in Figure 2, visualizations with similar statistical properties can look very different when visualizing the underlying data distributions.…”
Section: Value Of Visualizing Data To Understand Underlying Data Propertiesmentioning
confidence: 99%
“…Visualize uncertainty to support inference-making 5. Visualizing uncertainty is a useful aid for researchers to make statistical and inferential decisions 2,7 Visualize data in ways that enable you to see and understand the nature of the data dispersion and to test assumptions of the data.…”
Section: Fundingmentioning
confidence: 99%